A GRAPHICAL EXPRESSION SUPPORTING LISTENING AND MUSICAL PERCEPTION: MUSICOGRAM TECHNIQUE IN EARLY CHILDHOOD - Türkoğlu, Didem; Terzioğlu, Ahmet Mutlu; Can Yaşar, Münevver (International Online Journal of Education and Teaching, 2023)
Various techniques are employed to enhance music listening and perception skills in early childhood. One of these techniques is the musicogram method, proposed by Wuytack in the early 1970s following research into active music listening. This study aims to examine musicogram videos targeting early childhood shared on a social media platform, YouTube. The study employed a qualitative research method, and data was collected through document analysis. For data collection, videos were accessed on the video-sharing platform YouTube using keywords “müzikogram,” “müzogram,” “musicogram,” “musicograma.” Within the filtering criteria, musicograms in Turkish and different languages were included in the study based on their highest view counts across all time periods and sorted by ranking. As a result of the study, it was observed that classical Western music was predominantly used in musicograms prepared in different languages, whereas digital music and familiar children’s songs were preferred in Turkish musicograms. It was also found that the symbolic representation used in musicograms did not correspond to the melodic rhythmic patterns of the compositions. The use of musicograms for early childhood has gained significant popularity on social media; however, there is a need to enhance the content to be more comprehensive, including theoretical and practical information.